Osteoclastogenic Potential of Peripheral Blood Mononuclear Cells in Cleidocranial Dysplasia - Faienza, Maria Felicia (Ivyspring International Publisher, 2014)
Cleidocranial dysplasia (CCD) is an autosomal dominant skeletal dysplasia characterized by hypoplastic or aplastic clavicles, dental abnormalities, and delayed closure of the cranial sutures. In addition, mid-face hypoplasia, short stature, skeletal anomalies and osteoporosis are common. We aimed to evaluate osteoclastogenesis in a child (4 years old), who presented with clinical signs of CCD and who have been diagnosed as affected by deletion of RUNX2, master gene in osteoblast differentiation, but also affecting T cell development and indirectly osteoclastogenesis. The results of this study may help to understand whether in this disease is present an alteration in the bone-resorptive cells, the osteoclasts (OCs). Unfractionated and T cell-depleted Peripheral Blood Mononuclear Cells (PBMCs) from patient were cultured in presence/absence of recombinant human M-CSF and RANKL. At the end of the culture period, OCs only developed following the addition of M-CSF and RANKL. Moreover, real-time PCR experiment showed that freshly isolated T cells expressed the osteoclastogenic cytokines (RANKL and TNFα) at very low level, as in controls. This is in accordance with results arising from flow cytometry experiments demonstrating an high percentage of circulating CD4(+)CD28(+) and CD4(+)CD27(+) T cells, not able to produce osteoclastogenic cytokines. Also RANKL, OPG and CTX serum levels in CCD patient are similar to controls, whereas QUS measurements showed an osteoporotic status (BTT-Z score -3.09) in the patient. In conclusions, our findings suggest that the heterozygous deletion of RUNX2 in this CCD patient did not alter the osteoclastogenic potential of PBMCs in vitro.